The back translation from connotative into denotative words and phrases: English-Indonesian translation - Tambunsaribu, Gunawan; Hattalaibessy, Enrico Al Israel (Journal of Applied Studies in Language, 2025)
This study investigates the use of connotative words and phrases in the novel Raumanen and aims to translate them into their denotative equivalents. It further examines whether the translated (target) text retains the original meaning of the source text. Data were collected from the novel Raumanen, and the research employed a descriptive qualitative method. The steps included: (a) identifying connotative words and phrases in the source language, (b) re-translating them using denotative expressions, and (c) comparing the meanings between the original translator’s version and the researchers’ re-translation. The findings indicate that translating connotative expressions into denotative language often results in unnatural phrasing and ambiguous meaning in the target text.